The limits of reality: Pareto and the myth of democracy - Andrea Lombardinilo (Quaderni di Sociologia, 2021)
The essay deals with the sociological analysis of democracy developed by Pareto in his Transformation of Democracy, particularly regarding the dialectics between residues and derivations, centrifugal and centripetal forces. Pareto dwells on the rise of plutocratic demagogy and socialism within the political scenario of a crumbling central sovereignty. Hence the need to probe his recourse to Vico’s theory of the historical circularity of states and classes which in turn finds its roots in ancient myths and legends. Prior to the advent of totalitarianism, Pareto seems to highlight the power of myth in the construction of collective movements and social actions. As a result, his concept of the transformation of democracy may echo Max Weber’s Science as a Profession (1919) and may have inspired Mannheim’s Ideology and Utopia (1929), where Pareto’s theories are abundantly exploited. Hence follows the purpose of a more detailed examination of Vico’s influence on Pareto’s social theory and to investigate Mannheim’s interpretation of his sociological effort soon after the end of World War II.